The endothelin receptor antagonist macitentan for the treatment of pulmonary arterial hypertension: A cross‐species comparison of its cytochrome P450 induction pattern - Alexander Treiber; Stephane Delahaye; Swen Seeland; Carmela Gnerre (Wiley, 2020)
Abstract The dual endothelin receptor antagonist macitentan was approved in 2013 for the treatment of pulmonary arterial hypertension. Macitentan is an inducer of cytochrome P450 expression in vivo in animal species but not in man. In rat and dog, changes in P450 expression manifest as autoinduction upon repeat dosing. The induction pattern, however, significantly differed between both species, and between male and female rats. While macitentan exposure steadily declined with dose in the dog, P450 induction was saturable in the rat reaching levels of 40%‐60% and 60%‐80% at steady‐state in male and female animals, respectively. The nature and number of P450 enzymes involved in macitentan clearance were identified as a major reason for the observed species differences. In the dog, macitentan was metabolized by a single P450 enzyme, that is, Cyp3a12, whereas several members of the Cyp2c and Cyp3a families were involved in the rat. Macitentan selectively upregulated Cyp3a expression in rat, whereas the expression of the Cyp2c enzymes involved in macitentan metabolism remained mostly unchanged, eventually leading to a higher contribution of Cyp3a upon induction. Macitentan also induced CYP3A4 expression in human hepatocytes via initial activation of the human pregnane X receptor. No such induction was evident in humans at the therapeutic macitentan dose of 10 mg as shown in a clinical drug‐drug interaction study with the CYP3A4 substrate sildenafil.